Samuel Sebagai Hakim : Studi Hermeneutika 1 Samuel 7:15-17 - Dedy Kurniawan Gaho; Lilis Tampubolon (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Samuel's role as Israel's final judge, a leader who carried out the dual function of political and spiritual leader with integrity. Using critical historical interpretation analysis methods. Through in-depth analysis of these verses, this paper identifies Samuel's Faithful Leadership, Active and Inclusive Ministry, Worship as a Life Priority and God as a Just Judge. This article also highlights the relevance of these principles in a modern context, such as the importance of responsible leadership, consistent service, and a God-centered life. By making worship of God the basis of life, Samuel provides an example of leadership that not only brings people to justice, but also maintains a spiritual relationship with God. This paper concludes that true leadership must be based on obedience to Allah and timeless dedication.